2010
DOI: 10.1590/s1983-14472010000400014
|View full text |Cite
|
Sign up to set email alerts
|

O acesso à assistência ao parto para parturientes adolescentes nas maternidades da rede SUS

Abstract: Estudo quantitativo, observacional e de delineamento transversal, cujo objetivo foi identificar os fatores que interferem na acessibilidade da gestante ao acompanhamento do parto na rede do Sistema Único de Saúde (SUS) na cidade do Rio de Janeiro (RJ). Foi realizado em maternidades da rede SUS-RJ, por meio de entrevista estruturada. A amostra constituiu-se de 328 puérperas adolescentes. As informações foram organizadas em banco de dados, e para análise se utilizou o software EPI INFO versão 6.03, e a razão de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
8
0
8
Order By: Relevance
“…It was also verified that 20.7% of them did not give birth in the first hospital sought. Age, level of education, marital status, income and race/color were some factors that did not interfere with access (6) . The city of residence is also a factor that can influence access, considering women differently if they live in cities other than that were the reference hospital for childbirth assistance is located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also verified that 20.7% of them did not give birth in the first hospital sought. Age, level of education, marital status, income and race/color were some factors that did not interfere with access (6) . The city of residence is also a factor that can influence access, considering women differently if they live in cities other than that were the reference hospital for childbirth assistance is located.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of access refers to the individual being admitted to the health system, but may also be defined in accordance with the final objective of the care and the results attained (1) . The insufficiencies in Brazilian obstetric care relate not only to access but also the poor distribution of beds that results in long journeys by pregnant women seeking vacancies to give birth, exposing them to risks and aggravation of their situation (2) . The search for a hospital by pregnant women for childbirth and the healthcare at the first hospital sought after has been improving in the country, and the south region has better access indicators, given that it has been identified that 96% of women gave birth at the first hospital sought (3) .…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, es respecto a la accesibilidad cultural donde aparecen más diferencias. En efecto, hay autores que la excluyen de su análisis, quedándose sólo con las restantes dimensiones 5,33 . Por su parte Sales Clementino & Nunes 18 la conceptualizan como accesibilidad sociocultural, ampliando su alcance.…”
Section: Tipologías De Accesibilidadunclassified
“…A palavra peregrinar remete à ideia de sacrifício, e, no caso das gestantes que peregrinam, o trajeto é dificultado pela dor, tornando-se uma saga 26 . Entende-se por peregrinação a necessidade de percorrer mais de um serviço de saúde até conseguir acesso para atendimento ao parto 27 .…”
Section: Introductionunclassified